Identifying the Risk Factors for Orbital Complications in Isolated Sphenoid Rhinosinusitis - Shiaw-Yu Chang; Chi-Che Huang; Yu-Hsi Fan; Pei-Wen Wu; Ta-Jen Lee; Po-Hung Chang; Chien-Chia Huang (Medicina, 2024)
Background and Objectives: Isolated sphenoid rhinosinusitis may have devastating consequences such as orbital complications due to its anatomical contiguity with vital structures. This study aimed to identify patients with isolated sphenoid inflammatory diseases at high risk for developing orbital complications and requiring aggressive management through investigation of the clinical and computed tomography (CT) characteristics of patients with isolated sphenoid rhinosinusitis. Materials and Methods: The medical records of patients who underwent endoscopic sinus surgery between 2005 and 2022 were retrospectively reviewed. Patients with isolated sphenoid rhinosinusitis were identified based on a manual review of the clinical and histopathological findings. Participants’ clinical and CT features were reviewed. Results: Among the 118 patients with isolated sphenoid rhinosinusitis, 15 (12.7%) developed orbital complications, including diplopia, extraocular motility limitation, ptosis, and visual impairment. Headaches and facial pain occurred significantly more frequently in patients with orbital complications than in those without orbital complications (p < 0.001). Patients with diabetes mellitus or malignant neoplasms were more likely to develop orbital complications than those without these comorbidities (p < 0.05). Bony dehiscence on CT images was significantly more common in patients with orbital complications than in those without. In the regression analysis, diabetes mellitus (OR, 4.62), malignant neoplasm (OR, 4.32), and bony dehiscence (OR, 4.87) were significant predictors of orbital complications (p < 0.05). Conclusions: Headaches and facial pain are the most common symptoms of isolated sphenoid rhinosinusitis. Orbital complications of isolated sphenoid rhinosinusitis are more common in patients with comorbidities such as diabetes mellitus or malignancy or in those with bony dehiscence on CT images.